Empowering anomaly detection algorithm: a review - Iqbal Basheer, Muhammad Yunus; Mohd Ali, Azliza; Osman, Rozianawaty; Abdul Hamid, Nurzeatul Hamimah; Nordin, Sharifalillah; Mohd Ariffin, Muhammad Azizi; Iglesias Martínez, José Antonio (Institute of Advanced Engineering and Science, 2024)
Detecting anomalies in a data stream relevant to domains like intrusion detection, fraud detection, security in sensor networks, or event detection in internet of things (IoT) environments is a growing field of research. For instance, the use of surveillance cameras installed everywhere that is usually governed by human experts. However, when many cameras are involved, more human expertise is needed, thus making it expensive. Hence, researchers worldwide are trying to invent the best-automated algorithm to detect abnormal behavior using real-time data. The designed algorithm for this purpose may contain gaps that could differentiate the qualities in specific domains. Therefore, this study presents a review of anomaly detection algorithms, introducing the gap that presents the advantages and disadvantages of these algorithms. Since many works of literature were reviewed in this review, it is expected to aid researchers in closing this gap in the future.